Women in peasant movements : Tebhaga, naxalite, and after - SinghaRoy, Debal K. (New Delhi : Manohar, 1992)
Case study of West Bengal, India.
Includes index.
Keywords: Women agricultural laborers -- Political activity -- India -- West Bengal -- History -- 20th century; Rural women -- Political activity -- India -- West Bengal -- History -- 20th century; Peasant uprisings -- India -- West Bengal -- History -- 20th century